2015
DOI: 10.1371/journal.pntd.0003759
|View full text |Cite|
|
Sign up to set email alerts
|

Insights into the Interactions of Fasciola hepatica Cathepsin L3 with a Substrate and Potential Novel Inhibitors through In Silico Approaches

Abstract: Background Fasciola hepatica is the causative agent of fascioliasis, a disease affecting grazing animals, causing economic losses in global agriculture and currently being an important human zoonosis. Overuse of chemotherapeutics against fascioliasis has increased the populations of drug resistant parasites. F. hepatica cathepsin L3 is a protease that plays important roles during the life cycle of fluke. Due to its particular collagenolytic activity it is considered an attractive target against the infective p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…This residue is specific of Fh CL3 and when mutated for Leu as in Fh CL1 it renders the enzyme almost inactive highlighting its importance for substrate positioning for catalysis [ 39 ]. A recent in silico search for Fh CL3 inhibitors provides additional evidence that the non-polar side chain of Trp 69 establishes critical interaction with ligands and adopts variable conformations to accommodate different groups in the enzyme binding site [ 62 ]. Furthermore, it showed that aromatic moieties with high hydrophobicity can establish favorable interactions with non-polar residues from Fh CL3 binding cleft [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This residue is specific of Fh CL3 and when mutated for Leu as in Fh CL1 it renders the enzyme almost inactive highlighting its importance for substrate positioning for catalysis [ 39 ]. A recent in silico search for Fh CL3 inhibitors provides additional evidence that the non-polar side chain of Trp 69 establishes critical interaction with ligands and adopts variable conformations to accommodate different groups in the enzyme binding site [ 62 ]. Furthermore, it showed that aromatic moieties with high hydrophobicity can establish favorable interactions with non-polar residues from Fh CL3 binding cleft [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent in silico search for Fh CL3 inhibitors provides additional evidence that the non-polar side chain of Trp 69 establishes critical interaction with ligands and adopts variable conformations to accommodate different groups in the enzyme binding site [ 62 ]. Furthermore, it showed that aromatic moieties with high hydrophobicity can establish favorable interactions with non-polar residues from Fh CL3 binding cleft [ 62 ]. The greater number of interactions between inhibitor and residues from Fh CL3 sub-sites compared with Fh CL1, might explain its lower IC 50 ( Table 1 ), its behavior as a slowly reversible inhibitor ( Fig 2 ), and its highest percentage of inhibition reached after 120 min ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three FP‐2 residues, that is, Q36, G83, and N173, were predicted to form hydrogen bonds with the backbone nitrogen and oxygen atoms at P2 to P1′ sites of the ligands with relatively high occupancies (Supporting Information, Table S2). Equivalent hydrogen bonds occur at the interfaces of crystal structures of C1 cysteine proteases in complex with peptide‐based inhibitors, and have been predicted for FP‐2 and other homologous enzymes complexed with nonpeptidic compounds . Remarkably, G83 and N173 each formed up to two hydrogen bonds with the inhibitors ((a–d), Fig.…”
Section: Resultsmentioning
confidence: 81%
“…The MMPBSA.py program of Amber12 package was used for MM-GB(PB)SA free energy calculations [ 48 , 50 ] after converting the GROMACS trajectories into the Amber format by using VMD v1.9.1 as described elsewhere [ 51 ]. In all cases we followed the single trajectory (ST) approach, in which the trajectories for the free enzyme and the free ligand are extracted from that of the complex [ 48 , 50 ].…”
Section: Methodsmentioning
confidence: 99%